Characterization of a Neutral Sphingomyelinase Activity in Human Serum and Plasma - Mühle, Christiane; Kornhuber, Johannes (International Journal of Molecular Sciences, 2023)
Alterations of sphingolipids and their metabolizing enzymes play a role in various diseases. However, peripheral biomarkers for such changes are limited. Particularly, in the increasingly reported involvement of neutral sphingomyelinase (NSM) with four described isoforms in tissues or cells, a peripheral marker is lacking. We here describe the detection of an NSM activity in human serum and plasma samples which hydrolyses fluorescently labeled sphingomyelin to ceramide in a time- and volume-dependent manner. Reaction rates were linear up to 10 days, and serum volumes above 2 vol-% were inhibitory. Biochemical properties were different from acid sphingomyelinase (ASM) with respect to detergent specificity (sodium deoxycholate), pH profile (pH 7–9), and cation dependence: Serum NSM activity was inhibited by EDTA ≥ 1 µM and restored in EDTA-anticoagulated plasma with the addition of ≥ 100 µM Co2+. It was independent of Mg2+, the typical cofactor of cellular NSM species, and even inhibited by [Mg2+] ≥ 20 mM. Serum NSM activity was not correlated with ASM activity and was independent of sex and age in 24 healthy adults. Since human peripheral NSM activity is very low and activities in rodents are even lower or undetectable, future research should aim to increase the reaction rate and determine the source of this enzymatic activity. The established activity could serve as a future biomarker or therapeutic target in diseases affected by sphingolipid derangements.
CRIS-Team Scopus Importer:2023-02-24
Keywords: blood biomarker; ceramide; cobalt cofactor; EC 3.1.4.12; enzyme inhibitors; NSM; SMPD3; sphingolipid metabolism; sphingomyelin; sphingomyelin phosphodiesterase